Food temperature altered macronutrients induced changes in satiety hormones; glucagon - like peptide -1 and cholecystokinin and their correlation with subjective satiety - Naila Hamid; Muhammad O. Malik; Bibi Hajira; Inayat Shah; Mahnoor Azhar (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The benefits of dietary macronutrients for weight management depend on the integrity of gut hormones. The role of food temperature in the release of satiety hormones and satiety needs elucidation. We aimed to determine the impact of different food temperatures with varying macronutrient compositions on satiety-related gut hormones glucagon-like peptide-1 (GLP-1) and cholecystokinin (CCK) and find the correlation of satiety hormones with appetite scores and remainder-day food (energy) intake. MATERIALS AND METHODS: Thirteen healthy participants (eight males and five females) aged 25-35 years with body mass index 18.5-24.9 kg/m2 with no medical illnesses or eating disorders consumed three compositions of meals (high carbohydrate, high fat, and high protein meals) each at three temperatures (cold, warm, and hot) in a randomized, double-blinded, controlled crossover design. Plasma concentrations of peptide hormones were determined at 0, 30, and 240 minutes by enzyme-linked immunosorbent assay, and 24-hours food recall was used for remainder-day food intake (remainder energy). Data were analyzed using SPSS version 27.0. The change in plasma levels of gut hormones with time was assessed using Friedman test; Kruskal-Wallis test was employed to compare GLP-1 and CCK hormonal levels across nine meals. RESULTS: A comparison of the three meals at the three temperatures (total of nine groups), showed that the GLP-1 and CCK plasma concentrations were significantly different (P < 0.001). GLP-1 and CCK responses increased more after hot meals than cold meals. Overall, high-fat meals had more effective gut hormone secretions. The area under the curve was increased for GLP-1 in high-fat meals and for CCK in hot meals. The peptide hormones (GLP-1 and CCK) were positively correlated with satiety scores and inversely with remainder food intake. CONCLUSION: The temperature of food was found to be an effective stimulus for the regulation of CCK and GLP-1 secretion. Hot food temperature increased satiety hormones (CCK and GLP-1), independent of food macronutrient composition.